Primer on large-scale assessments of educational achievement - Clarke, Marguerite (Education researcher); Luna-Bazaldua, Diego (National assessments of educational achievement., 2021)
"To improve their education systems, countries around the world have increasingly initiated national largescale assessment programs or participated in international or regional large-scale assessment studies for the first time. Well-constructed large-scale assessments can provide credible information on student achievement levels, which, in turn, can promote better resource allocation to schools, stronger education service delivery, and improved learning outcomes. The World Bank developed this Primer on Large-Scale Assessments of Educational Achievement as a firststop resource for those wanting to understand how to design, administer, analyze, and use the results from these assessments of student achievement. The book addresses frequently asked questions from people working on large-scale assessment projects and those interested in making informed decisions about them. Each chapter introduces a stage in the assessment process and offers advice, guidelines, and country examples. This book also reports on emerging trends in large-scale assessment and provides updated information on regional and international large-scale assessment programs"--Publisher's description.